The consciousness of schoolchildren and giftedness - Anna A. Proskurina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper addresses the problem of theoretical determination of the presence and quality of the necessary and steady interrelation between the consciousness and the giftedness of schoolchildren. It is argued for the need of a social philosophic approach to the solution of this problem in the perspective of subjective action. The problem is tackled by means of the theoretical analysis of speech functions in the performance of subjective action by a social individual. The study reveals, on the one hand, which subjective action elements the acting individual is necessarily aware of. On the other hand, it is shown which elements of self-concept, when purposefully and artificially developed, are an obstacle for the performance of subjective action